2015
DOI: 10.1038/srep17696
|View full text |Cite
|
Sign up to set email alerts
|

Rapid accumulation and low degradation: key parameters of Tomato yellow leaf curl virus persistence in its insect vector Bemisia tabaci

Abstract: Of worldwide economic importance, Tomato yellow leaf curl virus (TYLCV, Begomovirus) is responsible for one of the most devastating plant diseases in warm and temperate regions. The DNA begomoviruses (Geminiviridae) are transmitted by the whitefly species complex Bemisia tabaci. Although geminiviruses have long been described as circulative non-propagative viruses, observations such as long persistence of TYLCV in B. tabaci raised the question of their possible replication in the vector. We monitored two major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 52 publications
(79 reference statements)
4
30
2
1
Order By: Relevance
“…However, whether begomoviruses can be transmitted transovarially is still in great controversy. Although most of the studies reported absence of transovarial transmission (35)(36)(37)(38)(39), several studies reported the presence of transovarial transmission, but the efficiencies varied considerably between studies (40-42) (Table S1). Our study proved that TYLCV can be effectively transmitted via ovary of whitefly adults of elder age, but not by whitefly adults of very young age (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether begomoviruses can be transmitted transovarially is still in great controversy. Although most of the studies reported absence of transovarial transmission (35)(36)(37)(38)(39), several studies reported the presence of transovarial transmission, but the efficiencies varied considerably between studies (40-42) (Table S1). Our study proved that TYLCV can be effectively transmitted via ovary of whitefly adults of elder age, but not by whitefly adults of very young age (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TYLCV purified virions were acquired by whiteflies on an artificial sucrose diet in an attempt to provide them only encapsidated virus VS forms. Thus, acquisition from plants as done in previous studies 10 15 17 was not performed to diminish or prevent the acquisition of CS forms and/or viral transcription and/or replication complexes that could be present in infected plants. Also, previous to virus acquisition, purified virions were treated with DNase I to eliminate or reduce the presence of non-encapsidated viral nucleic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Also, previous to virus acquisition, purified virions were treated with DNase I to eliminate or reduce the presence of non-encapsidated viral nucleic acids. Moreover, after AAP and until analysis, whiteflies were maintained on an artificial diet and not on a virus non-host plants as done in previous studies 16 17 to eliminate plant factors that could help to complete the virus life cycle within the whiteflies. The infectivity of purified-DNase I-treated virions was confirmed through B. tabaci transmission to tomato plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations